Short Review : Parosphromenus juelinae (Taxonomy, Habitat Ecology, and Conservation Efforts) - Aminin Aminin; Muh. Sulaiman Dadiono (PT. Gyandharma Global Media, 2025)
Parosphromenus juelinae is a small ornamental fish species from the genus Parosphromenus (licorice gouramis group) found in peat swamp waters in Southeast Asia. This study aims to review the morphological characteristics, habitat ecology, reproductive behavior, and conservation challenges of this species. The research method was carried out through a literature review of primary and secondary literature. The results of the study indicate that P. juelinae has distinctive morphological characteristics in the form of brightly colored fins with unique patterns, lives in acidic water environments with low pH, and is highly dependent on peat swamp ecosystems that are currently threatened by deforestation. In conclusion, this species plays an important role as an indicator of peat swamp ecosystem health, so that natural habitat based conservation efforts and further research on its cultivation potential are needed.